(untitled) (Historia, 2021)
Environmental management in South Africa: twenty years of governmental response to the global challenge, 1972-1992 The article examines South African governmental initiatives in environmental management between the two historic environmental conferences hosted by the United Nations, namely the 1972 United Nations Conference on the Human Environment and the 1992 United Nations Conference on Environment and Development. the twenty years under discussion was an important development phase for environmental management on both national and international political levels. It was a period in which the focus gradually shifted from addressing the environment as a political issue in the 1970s, to acknowledging by 1992 that the world at large needed a new developmental model (namely sustainable development) if humankind was to survive.